Construction and Verification of the Constitutive Model of Pure Copper Deformation at Elevated Temperatures - Huang, S.H.; Wu, Y.; Zhao, Z.D.; Xia, X.S. (Проблемы прочности, 2019)
The deformation behavior of pure copper was studied in hot compression tests in the temperature range of 773–1173 K and strain rate interval of 0.001–1.0 s⁻¹, the corresponding flow stress curves were plotted. The new method to calculate critical and saturation stresses was devised, quantitative analysis of strain hardening and dynamic softening was presented, a three-stage constitutive model was constructed to predict the flow stress of pure copper. As predicted and measured flow stress comparison indicate, the physical constitutive model can accurately characterize hot deformation of pure copper. With dynamic recovery and/or recrystallization. Numerical simulation of an upsetting process is carried out by implementing the constitutive model into commercial software. This model can be put to practical use and be quite promising for improving efficiency of a hot forging process for pure copper components. Изучено деформационное поведение чистой меди при испытании горячих проб на сжатие в диапазоне температур 773 1173 К и скорости деформации 0.001–1.0 с⁻¹, построены соответствующие кривые напряжения пластического течения. Разработан новый метод расчета критического напряжения и напряжения насыщения, представлен количественный анализ деформационного упрочнения и динамического разупрочнения, построена трехступенчатая определяющая модель прогнозирования напряжения пластического течения чистой меди. Как показывает сравнение прогнозируемого и измеренного напряжений пластического течения, с помощью такой модели можно точно описать горячее деформирование чистой меди при динамическом возврате и/или рекристаллизации. Выполнено численное моделирование процесса высадки путем реализации данной модели в рамках коммерческого программного обеспечения. Модель весьма перспективна и может использоваться для повышения эффективности процесса горячей ковки деталей из чистой меди. Вивчено деформаційне поведінку чистої міді при випробуванні гарячих проб на стиск в діапазоні температур 773-1173 К і швидкості деформації 0.001–1.0 с⁻¹, побудовані відповідні криві напружень пластичної течії. Розроблено новий метод розрахунку критичної напруги і напруги насичення, представлений кількісний аналіз деформаційного зміцнення і динамічного знеміцнення, побудована триступенева визначає модель прогнозування напружень пластичної течії чистої міді. Як показує порівняння прогнозованого і виміряного напружень пластичної течії, за допомогою такої моделі можна точно описати гаряче деформування чистої міді при динамічному поверненні і / або рекристалізації. Виконано чисельне моделювання процесу висадки шляхом реалізації даної моделі в рамках комерційного програмного забезпечення. Модель вельми перспективна і може використовуватися для підвищення ефективності процесу гарячого кування деталей з чистої міді.